War on Instagram: Framing conflict photojournalism with mobile photography apps. (December 2014) - Alper, Meryl
This paper examines recent acclaim for professional embedded photojournalists who visually document the experience of US soldiers in Afghanistan using the popular mobile photo application Hipstamatic. These photos have stirred controversy among fellow journalists and cultural critics regarding the use of photo filters in Hipstamatic and similar app Instagram, their contribution to the de-professionalization of photojournalism, and the depiction of war as stylishly vintage. The debates about Hipstamatic and Instagram in war photography open up a whole series of enduring questions about distinctions between photography and illustration, photography and photojournalism, professional and amateur, and reporting and editorializing. In consideration of the shifting nature of digital photography, photojournalism, and specifically war photojournalism, I argue that this discourse about the use of mobile apps overlooks another important ethical issue: the implications of non-soldiers mimicking the imagined hand of the modern smartphone-equipped US soldier, particularly in light of soldiers' own complex media-making practices.